1987
DOI: 10.1083/jcb.105.6.2501
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent cell-cell adhesion molecules (cadherins): subclass specificities and possible involvement of actin bundles.

Abstract: Abstract. Cadherins are a family of cell-cell adhesion molecules and are divided into subclasses with distinct adhesive specificities and tissue distribution. Here we examined the distribution of cadherins at contact sites between cells expressing the same or different cadherin subclasses. Each cadherin was concentrated at the boundary between cells expressing an identical cadherin subclass, irrespective of the cell types connected. However, such localization decreased or disappeared at the boundary between ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
200
0
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(214 citation statements)
references
References 28 publications
12
200
0
2
Order By: Relevance
“…Detergent extraction of cells was carried out according to Hirano et al (1987). In brief, cells were incubated with 0.5% NP-40 in Hepes-buffered (pH 7.4) saline containing 1 mM Ca 2 for 30 min on ice before ®xation, and then immunostained as described above.…”
Section: Immuno¯uorescence Stainingmentioning
confidence: 99%
“…Detergent extraction of cells was carried out according to Hirano et al (1987). In brief, cells were incubated with 0.5% NP-40 in Hepes-buffered (pH 7.4) saline containing 1 mM Ca 2 for 30 min on ice before ®xation, and then immunostained as described above.…”
Section: Immuno¯uorescence Stainingmentioning
confidence: 99%
“…The binding specificity of cadherins is determined by a restricted region of the amino terminal part of the molecule (Nose et al, 1990). The cytoplasmic domain also appears to be essential for cadherin function through its capacity to interact with appropriate cytoskeletal molecules such as catenins and fodrin Ozawa et al, 1989;Hirano et al, 1987, Mc Neil1 et al, 1990. However, one cadherin has been shown to be anchored to the plasma membrane by a glycosyl-phosphatidyl inositol (Ranscht and Dours-Zimmerman, 1991) and to be nevertheless capable of mediating cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the amino acid sequence of the cytoplasmic domain is highly conserved among the cadherins, suggesting that this region serves an important shared function. Recent molecular biological experiments have shown that this domain is essential for cell adhesion activity , and it is likely that it exerts this effect through interacting with cytoskeletat proteins (Hirano et aL, 1987;Nagafuchi and Takeichi, 1989;Ozawa et al, 1989).…”
Section: Introductionmentioning
confidence: 99%